2019
DOI: 10.1097/aln.0000000000002947
|View full text |Cite|
|
Sign up to set email alerts
|

A Population-based Comparative Effectiveness Study of Peripheral Nerve Blocks for Hip Fracture Surgery

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background Adverse outcomes and resource use rates are high after hip fracture surgery. Peripheral nerve blocks could improve outcomes through enhanced analgesia and decreased opioid related adverse events. We hypothesized that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Given the large number of hip fractures that occur, population-level studies of hip fracture care and outcomes are common. [4][5][6][7][8][9] While core outcome sets (ie, an agreed minimum set of outcomes that should be measured and reported in all clinical trials of a specific disease or trial population 10 ) have been developed for patients with hip fracture, mortality is the only core outcome measure typically available in population-level data. 11 12 Furthermore, other routinely available population-level outcomes (eg, length of stay) are not patient-centred.…”
Section: Introductionmentioning
confidence: 99%
“…Given the large number of hip fractures that occur, population-level studies of hip fracture care and outcomes are common. [4][5][6][7][8][9] While core outcome sets (ie, an agreed minimum set of outcomes that should be measured and reported in all clinical trials of a specific disease or trial population 10 ) have been developed for patients with hip fracture, mortality is the only core outcome measure typically available in population-level data. 11 12 Furthermore, other routinely available population-level outcomes (eg, length of stay) are not patient-centred.…”
Section: Introductionmentioning
confidence: 99%
“…7 The present study obtained different results from those conducted in North America, which found that receipt of PNB for hip fracture surgery is associated with decreased LOS and health system costs. 23 We hypothesize that this discrepancy is attributable to differences in health care systems. Chinese patients typically return home after full recovery, rather than transfer to a rehabilitation center in a short period after surgery, which leads to higher cost and prolonged LOS.…”
Section: Discussionmentioning
confidence: 98%
“… 22 But other studies, conducted as secondary outcomes without adjusted analysis, found no significant difference in 30-day mortality between PNB and non-PNB groups. 13 , 23 It is well known that one common limitation of observational studies is selection bias, a consequence of lack of randomization, which results in higher-risk patients being more likely to undergo one of the interventions due to the theorized benefits. The retrospective studies in question enrolled patients with different types of hip fracture (femoral neck vs intertrochanteric fracture), surgery options (total hip arthroplasty, hemiarthroplasty, and internal fixation), and comorbidities between the PNB and non-PNB groups.…”
Section: Discussionmentioning
confidence: 99%
“…Murouchi [ 32 ] et al reported that the peak concentration of ropivacaine after QLB was lower than that of TAPB at a comparable time, and the duration of analgesia was significantly longer. Second, the procedure performed on individuals in group QF further reduced the sensitivity of nerves to surgical stimulation, prevented central and peripheral sensitization, and reduced or eliminated pain caused by nociceptive stimulation [ 33 ]. Last, patients' oral paracetamol 1 g regularly at 6 h intervals after operation also prolonged the time to the first opioid requirement.…”
Section: Discussionmentioning
confidence: 99%